Pro-Resolving Lipid Mediator Resolvin E1 Mitigates the Progress of Diethylnitrosamine-Induced Liver Fibrosis in Sprague-Dawley Rats by Attenuating Fibrogenesis and Restricting Proliferation - Maria José Rodríguez (International Journal of Molecular Sciences, 2020)
Liver fibrosis is a complex process associated to most types of chronic liver disease, which is characterized by a disturbance of hepatic tissue architecture and the excessive accumulation of extracellular matrix. Resolvin E1 (RvE1) is a representative member of the eicosapentaenoic omega-3 lipid derivatives, and is a drug candidate of the growing family of endogenous resolvins. Considering the aforementioned, the main objective of this study was to analyze the hepatoprotective effect of RvE1 in a rat model of liver fibrosis. Male Sprague-Dawley rats received diethylnitrosamine (DEN, 70 mg/mg body weight intraperitoneally (i.p)) as an inductor of liver fibrosis once weekly and RvE1(100 ng/body weight i.p) twice weekly for four weeks. RvE1 suppressed the alterations induced by DEN, normalizing the levels of alanine aminotransferase (ALT), albumin, and lactate dehydrogenase (LDH), and ameliorated DEN injury by decreasing the architecture distortion, inflammatory infiltration, necrotic areas, and microsteatosis. RvE1 also limited DEN-induced proliferation through a decrease in Ki67-positive cells and cyclin D1 protein expression, which is related to an increase of the levels of cleaved caspase-3. Interestingly, we found that RvE1 promotes higher nuclear translocation of nuclear factor κB (NF-κB)p65 than DEN. RvE1 also increased the levels of nuclear the nuclear factor erythroid 2–related factor 2 (Nrf2), but with no antioxidant effect, measured as an increase in glutathione disulfide (GSSG) and a decrease in the ratio of glutathione (GSH)/GSSG. Taken together, these results suggest that RvE1 modulates the fibrogenesis, steatosis, and cell proliferation in a model of DEN induced fibrosis.